2015
DOI: 10.1007/s00198-015-3158-2
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized, Phase III, multicenter study in 358 pediatric subjects receiving isotretinoin therapy demonstrates no effect on pediatric bone mineral density

Abstract: There is no difference in the effect of two formulations of isotretinoin on spine bone density after 6 months of treatment. BMD increased and the small change in spine Z-score over treatment disappeared after height adjustment. Mean positive Z-scores and HAZ in the study were likely due to the exclusion of low and inclusion of high Z-score subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…While high-dose retinoid exposure in animal studies have identified changes in bone mineral density, human clinical studies have observed variable results in different populations, with different retinoid drugs, and measurement techniques. Decreased bone mineral density associated with systemic retinoid treatment has been reported in some studies and not in others 87,88. The most relevant clinically important endpoint of decreased bone mineral density…”
mentioning
confidence: 99%
“…While high-dose retinoid exposure in animal studies have identified changes in bone mineral density, human clinical studies have observed variable results in different populations, with different retinoid drugs, and measurement techniques. Decreased bone mineral density associated with systemic retinoid treatment has been reported in some studies and not in others 87,88. The most relevant clinically important endpoint of decreased bone mineral density…”
mentioning
confidence: 99%
“…Four studies which analyzed a change of BMD at the lumbar spine in patients receiving oral isotretinoin showed its slight increase (1.1–3.0%) in contrast to the reported decrease at long bones [6, 22, 26, 27]. This change remained however in a normal range for young adolescents who typically manifest an increase in bone density 0.5–7.0% yearly [27].…”
Section: Resultsmentioning
confidence: 99%
“…In opposite, a prospective study by Leachman et al from 1999 presented that bone density in young men (aged 17–25 years) after receiving oral isotretinoin for cystic acne was lower at all sites (spine, femoral neck, and Ward triangle) was considerably more variable at the spine even before treatment. A potential explanation could be a significant decrease within 5 days of treatment ( p < 0.05) of markers of bone turnover, e.g., serum osteocalcin, the carboxyterminal propeptide of type I collagen, bone-specific alkaline phosphatase, the carboxyterminal telopeptide of type I collagen, and urine levels of calcium and hydroxyproline, serum calcium and parathyroid hormone, which were presented in a clinical trial of Kindmark et al On the positive side is the fact that the abnormal levels of these markers returned to baseline values within 14 days [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%